Soviet health care and perestroika. - Schultz, D S (1990)
Health and health care in the Soviet Union are drawing special attention during these first years of perestroika, Mikhail Gorbachev's reform of Soviet political and economic life. This report briefly describes the current state of Soviet health and medical care, Gorbachev's plans for reform, and the prospects for success. In recent years the Soviet Union has experienced a rising infant mortality rate and declining life expectancy. The health care system has been increasingly criticized for its uncaring providers, low quality of care, and unequal access. The proposed measures will increase by 50 percent the state's contribution to health care financing, encourage private medicine on a small scale, and begin experimentation with capitation financing. It seems unlikely that the government will be able to finance its share of planned health improvements, or that private medicine, constrained by the government's tight control, will contribute much in the near term. Recovery of the Soviet economy in general as well as the ability of health care institutions to gain access to Western materials will largely determine the success of reform of the Soviet health care system.